Do Global Food Price Shocks Matter for Inflation and Economic Growth in Indonesia? - Nur Fatini Binti Rosli; Salsabila Syafa Sinaga; Muhammad Alfi Azma (TALENTA PUBLISHER UNIVERSITAS SUMATERA UTARA, 2026)
This study investigates the relationship between global food prices, inflation, exchange rates, and economic growth in Indonesia within the framework of short-term and long-term adjustments. In the midst of increasing volatility in world food prices due to global supply chain disruptions, climate change, and geopolitical tensions, understanding the mechanism of global food price transmission to domestic macroeconomic stability is becoming increasingly important, especially for developing countries that are dependent on food imports such as Indonesia. This study uses monthly time series data for the period 2020–2025 which includes the global food price index, inflation, the exchange rate of the rupiah against the United States dollar, and real gross domestic product. The Error Correction Model (ECM) approach is used to analyze the dynamics of the relationship between variables by considering short-term adjustments as well as long-term equilibrium. Prior to estimation, stationarity tests were performed using the Augmented Dickey–Fuller (ADF) method and cointegration tests to ensure the validity of model specifications. The use of ECM allows the identification of error correction mechanisms when deviations from the long-term equilibrium occur due to external shocks, such as fluctuations in global food prices. This research is expected to make an empirical contribution to the macroeconomic literature, especially related to inflation and global price transmission in developing countries. In addition, the findings of this study are expected to be a reference for the formulation of food price stabilization policies, import dependence management, and strengthening monetary and fiscal policy coordination in maintaining inflation stability and Indonesia's economic growth amid global uncertainty.